2019
DOI: 10.3390/app9194102
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Diagnostic Accuracy of Physical Examination and MRI in the Most Common Knee Injuries

Abstract: Purpose: This study evaluated the diagnostic accuracy of physical examination and magnetic resonance imaging (MRI) in knee injuries. Methods: Ninety-six patients at a regional hospital were included in the study. Each participant underwent a physical examination in which menisci and ACL were evaluated. Knee joint MRI was collected from each patient. Physical examination and MRI scans were then compared with knee arthroscopy findings as a golden standard for meniscal and ligamentous lesions. The data were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 46 publications
1
40
0
Order By: Relevance
“…The accuracy of MRI for the diagnosis of meniscal tears has been reported to be 80–96% in other studies, but this depends upon the specific MRI protocols used 11–16 . Although these figures may appear impressive, clinical assessment has similar levels of accuracy at a fraction of the cost 14,17 . Our study had similar findings.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The accuracy of MRI for the diagnosis of meniscal tears has been reported to be 80–96% in other studies, but this depends upon the specific MRI protocols used 11–16 . Although these figures may appear impressive, clinical assessment has similar levels of accuracy at a fraction of the cost 14,17 . Our study had similar findings.…”
Section: Discussionsupporting
confidence: 79%
“…Krakowski et al . evaluated the diagnostic accuracy of physical examination and MRI in knee injuries 17 . Like us, they also reported that MRI was no more accurate than physical assessment of the knee, for the diagnosis of meniscal tears, medial or lateral.…”
Section: Discussionmentioning
confidence: 78%
“…Femoral condyles and the medial knee compartment were found to be most commonly affected. Unfortunately, there are no specific clinical tests for the evaluation of articular cartilage, and distinguishing between chondral or meniscal lesions is impossible during physical examination [34]. For this purpose, MRI becomes the only available diagnostic modality for a routine cartilage examination [35].…”
Section: Discussionmentioning
confidence: 99%
“…An early and accurate diagnosis is necessary to guide toward an efficient management of knee disorders and limit disability as well as loss of quality of life in affected individuals [ 4 , 5 ]. Yet, obtaining a valid initial knee disorder diagnosis remains a common challenge [ 6 ].…”
Section: Introductionmentioning
confidence: 99%